2017
DOI: 10.24088/ijbea-2017-21005
|View full text |Cite
|
Sign up to set email alerts
|

Validating a framework of the integration of Corporate Social Responsibility and Culture: The Case of Hotel Industry

Abstract: Abstract:The aim of this study is to determine the cluster of homogenous financial centers by using hierarchical clustering analysis, and to define in which same cluster Istanbul city takes part with other financial centers. Thirty eight countries financial center and sixteen variables were included in the analysis. For analyzing data, Ward's method of hierarchical clustering analysis technique was applied and a Squared Euclidian distance measure was used. According to the analysis results, countries were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Matthias (2015) believed that if the hotels CSR commitment is interpreted by guests as a real public interest, CSR has a positive impact on brand evaluation as well as on guest satisfaction and give advantages; low costs and efforts, high credibility and the crowd is used as a third-party control mechanism. Also, a study on 80 hotels in Bali revealed that customers, shareholders, employees, suppliers, community, and organizations are the most important stakeholders (Dewi, Mataram, and Siwantara (2017). One respondent added;…”
Section: One Respondent Also Explained;mentioning
confidence: 99%
“…Matthias (2015) believed that if the hotels CSR commitment is interpreted by guests as a real public interest, CSR has a positive impact on brand evaluation as well as on guest satisfaction and give advantages; low costs and efforts, high credibility and the crowd is used as a third-party control mechanism. Also, a study on 80 hotels in Bali revealed that customers, shareholders, employees, suppliers, community, and organizations are the most important stakeholders (Dewi, Mataram, and Siwantara (2017). One respondent added;…”
Section: One Respondent Also Explained;mentioning
confidence: 99%
“…Balinese cultural tourism is based on Balinese culture, Hindu religion, and Tri Hita Karana (human-God-environment/nature relationships) (Mudana et al, 2021). Balinese culture is rich with the combination of spirituality, religion, tradition, and art (Dewi et al, 2017;) Astuti et al, 2020). It is known that many hotels in Bali apply a Balinese culture as a hotel concept to attract tourists' visits.…”
Section: Introductionmentioning
confidence: 99%